Manejo agronomico del cultivo de tabaco (NIcotiana tabacum L.) en la Empresa Procesadora de Nicaragua, PROCENICSA, Jalapa, Nueva Segovia, Nicaragua, 2018 - Sanchez Membreño, Orlando Javier (2019)
Sumarios (Es, En)